Gut Microbiome Was Highly Related to the Regulation of Metabolism in Lung Adenocarcinoma Patients - Wang, Sheng; Chen, Huachun; Yang, Huizhen; Zhou, Kejin; Bai, Fan; Wu, Xiaoyu; Xu, Hanwen (Frontiers in Oncology, 2022)
Background: Lung adenocarcinoma (LUAD) is one of the most predominant subtypes of lung cancer. The gut microbiome plays a vital role in the pathophysiological processes of various diseases, including cancers. Methods: In the study, 100 individuals were enrolled. 75 stool and blood samples were analyzed with 16s-rRNA sequencing and metabolomics (30 from healthy individuals (H); 45 from LUAD patients). In addition, 25 stool samples were analyzed with metagenomics (10 from H; 15 from LUAD). The linear discriminant analysis (LDA) effect size (LefSe) and logistic regression analysis were applied to identify biomarker’s taxa and develop a diagnostic model. The diagnostic power of the model was estimated with the receiver operating characteristic curve (ROC) by comparing the area under the ROC (AUC). The correlation between biomarker’s taxa and metabolites was calculated using the Spearman analysis. Results: The α and β diversity demonstrated the composition and structure of the gut microbiome in LUAD patients were different from those in healthy people. The top three abundance of genera were Bacteroides (25.06%), Faecalibacterium (11.00%), and Prevotella (5.94%). The LefSe and logistic regression analysis identified 3 biomarker’s taxa (Bacteroides, Pseudomonas, and Ruminococcus gnavus group) and constructed a diagnostic model. The AUCs of the diagnostic model in 16s-rRNA sequencing and metagenomics were 0.852 and 0.841, respectively. 102 plasma metabolites were highly related to those three biomarker’s taxa. Seven metabolic pathways were enriched by 102 plasma metabolites, including Pentose phosphate pathway, Glutathione metabolism. Conclusions: In LUAD patients, the gut microbiome profile has significantly changed. We used three biomarker’s taxa to develop a diagnostic model, which was accurate and suit for the diagnosis of LUAD. Gut microbes, especially those three biomarker’s taxa, may participate in regulating metabolism-related pathway in LUAD patients, such as pentose phosphate pathway and glutathione metabolism.